Silanes for Building Protection: A Case Study in Systems Thinking Approach to Materials Science Education - Rosaria Ciriminna; Yael Albo; Alexandra Fidalgo; Laura Ilharco; Mario Pagliaro (Education Sciences, 2020)
Silanes, and organically modified silanes in particular, are commercially used to protect the built environment from deterioration and, in indoor applications, to minimize water vapor condensation and microbiological contamination. Increasing their uptake, we argue in this study, includes the need to adopt a systems-thinking view of this green chemistry technology. After identifying the key advantages of these coatings, we highlight important educational consequences to undergraduate courses and doctoral programs in chemistry and materials science which are common in many research topics, well beyond nanocoating science and technology.